Obstructive jaundice causes reduced expression of polymorphonuclear leucocyte adhesion molecules and a depressed response to bacterial wall products in vitro. Issue 5 (May 1996) - Plusa, S; Webster, N; Primrose, J
Abstract : BACKGROUND–Obstructive jaundice is associated with an increased incidence of infection and endotoxaemia, which may result from impaired host immunity. Neutrophil adhesion to vascular endothelium is a key part of the inflammatory response. AIMS–To investigate neutrophil adhesion molecule expression and activation in obstructive jaundice. PATIENTS–Nine adult patients with obstructive jaundice and 11 control subjects. METHODS–The expression of the neutrophil adhesion receptors L-selectin, CD11a, CD11b, CD11c, and CD15 was determined using flow cytometry. CD11b expression in response to stimulation with fMLP and endotoxin was measured. RESULTS–The basal expression of L-selectin, CD11a, and CD15 was significantly decreased in jaundiced patients (p < 0.05) and the expression of CD11b in response to stimulation with fMLP and endotoxin was significantly impaired in the jaundiced group. Endotoxin stimulation without plasma did not reverse the impaired response showing that it is not caused by endotoxin inactivation by plasma proteins. CONCLUSIONS–Neutrophils from patients with obstructive jaundice show decreased adhesion receptor expression and an impaired response to stimulation with bacterial products. This cellular dysfunction may be responsible for the high incidence of septic complications in these patients.